1984
DOI: 10.3109/03009748409100397
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Involvement in Rabbit Knee following Immobilization and Resulting in Osteoarthritis

Abstract: The inflammatory involvement of the synovium in immobilization-induced experimental osteoarthritis in rabbit knees has been investigated. One knee of each of 33 rabbits was immobilized for up to 5 weeks in extension and then allowed to remobilize for up to 8 weeks. Histological examination revealed the presence of marked inflammatory changes in the synovium which were evident after 4 days of immobilization. These were characterized by a rapid proliferation of synovial lining cells followed by mononuclear cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 10 publications
2
13
1
8
Order By: Relevance
“…7,[13][14][15][16][17] Most nontraumatic models result in contractures which reverse to almost normal after remobilization. 12,[18][19][20] The combination of immobilization and trauma has been shown to promote a more permanent loss of motion.…”
Section: Discussionmentioning
confidence: 99%
“…7,[13][14][15][16][17] Most nontraumatic models result in contractures which reverse to almost normal after remobilization. 12,[18][19][20] The combination of immobilization and trauma has been shown to promote a more permanent loss of motion.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of experimental studies on joint immobilization have been reported [6][7][8][9][10][11][12]. However, phenomena occurred in a joint cavity after joint immobilization have not been agreed in opinion.…”
Section: Introductionmentioning
confidence: 99%
“…Wie Reyher [31] beobachtete auch er keine Gelenkentzündungen durch Immobilisation, die allerdings ab und zu durch gelenknah gelegene Frakturen auftreten könnten [26]. Müller (1924) [25] beobachteten eine Hyperplasie der Synovia, deren Fältelung (Villi) und Pannusbildung kurz nach Beginn der 5-wöchigen Schienenimmobilisation zunahmen, dann abfielen und mit der Remobilisation wieder deutlich anstiegen. In der infra-und suprapatellaren Synovia zeigten sich schon nach 4 Tagen Entzündungszeichen, die nach 10 Tagen anstiegen, anschließend leicht abfielen und mit der Remobilisation erneut über das Immobilisationsniveau zunahmen.…”
Section: Veränderungen In Der Synoviaunclassified
“…In der infra-und suprapatellaren Synovia zeigten sich schon nach 4 Tagen Entzündungszeichen, die nach 10 Tagen anstiegen, anschließend leicht abfielen und mit der Remobilisation erneut über das Immobilisationsniveau zunahmen. Die Autoren konnten 3 -17 Tage nach Immobilisationsbeginn keinen erhöhten Gehalt an Prostaglandinen in der Synovialflüssigkeit finden [25].…”
Section: Veränderungen In Der Synoviaunclassified
See 1 more Smart Citation